2013
DOI: 10.4002/040.056.0210
|View full text |Cite
|
Sign up to set email alerts
|

Species Catalogue of Orthalicoidea in Argentina (Gastropoda: Stylommatophora)

Abstract: We provide here a catalogue of all available species nomina of Orthalicoidea occurring in Argentina. Ongoing taxonomic revisions on the genera Bostryx Troschel, 1847, Clessinia Doering, 1874, Pilsbrylia Hylton Scott, 1952, and Spixia Pilsbry & Vanatta, 1898, highlighted the necessity of an updated catalogue for the region. A total of 101 orthalicoidean species classified into four families, Bothriembryontidae, Bulimulidae, Odontostomidae and Simpulopsidae are present in Argentina. The catalogue provided here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 41 publications
5
35
0
16
Order By: Relevance
“…Based on molecular analysis performed by Breure & Romero (2012), Breure (2012) indicated that B. strobeli could be classified as Naesiotus Albers. However, according to the sculpture of the protoconch observed, typical of the genus Bostryx, and several anatomical characters such as a penis with cup shape and internally with triangular penial gland and a portion with sculpture (consisting in folds) and other without sculpture, and an epiphallus with variable diameter and two different sculptures in the inner wall, the present study concludes that of B. strobeli must be maintained in Bostryx as proposed by Cuezzo et al (2013). Miquel (1995) synonymized B. strobeli and Bulimulus (Scansicochlea) lolae Hylton Scott, 1967 because their shell characters were very similar.…”
Section: Bostryx Strobeli (Parodiz 1956) (Figs 6 20-23)mentioning
confidence: 88%
See 4 more Smart Citations
“…Based on molecular analysis performed by Breure & Romero (2012), Breure (2012) indicated that B. strobeli could be classified as Naesiotus Albers. However, according to the sculpture of the protoconch observed, typical of the genus Bostryx, and several anatomical characters such as a penis with cup shape and internally with triangular penial gland and a portion with sculpture (consisting in folds) and other without sculpture, and an epiphallus with variable diameter and two different sculptures in the inner wall, the present study concludes that of B. strobeli must be maintained in Bostryx as proposed by Cuezzo et al (2013). Miquel (1995) synonymized B. strobeli and Bulimulus (Scansicochlea) lolae Hylton Scott, 1967 because their shell characters were very similar.…”
Section: Bostryx Strobeli (Parodiz 1956) (Figs 6 20-23)mentioning
confidence: 88%
“…This author considered that Peronaeus (Lissoacme) puntanus Parodiz, 1947 is a synonym of B. pastorei, given the fact that both species have similar shells. This synonymy was maintained by Cuezzo et al (2013) and on basis of the observation of type material of both species, has been reformulated in the present study. Bostryx pastorei shows high variability in shell coloration, body whorl area, aperture shape and spire height.…”
Section: (Figs 6-14)mentioning
confidence: 99%
See 3 more Smart Citations